Childhood craniopharyngioma: a retrospective study of children followed in Hôpital Universitaire de Bruxelles - Magerman, Clémentine; Boros, Emese; Preziosi, Marco; Lhoir, Sophie; Gilis, Nathalie; De Witte, Olivier; Heinrichs, Claudine; Salmon, Isabelle; Fricx, Christophe; Vermeulen, Françoise; Lebrun, Laetitia; Brachet, Cécile; et al. (Frontiers in Endocrinology, 2024)
Introduction Craniopharyngioma (CPs) are benign brain tumors accounting for 5 - 11% of intracranial tumors in children. These tumors often recur and can cause severe morbidity. Postoperative radiotherapy efficiently controls and prevents progression and recurrence. Despite advancements in neurosurgery, endocrinological, visual, and neuropsychological complications are common and significantly lower the quality of life of patients. Methods We performed a retrospective study, including all patients younger than sixteen diagnosed with CP between July 1989 and August 2022 and followed up in Hopital Universitaire de Bruxelles. Results Nineteen children with CP were included, with median age of 7 years at first symptoms and 7.5 at diagnosis. Common symptoms at diagnosis were increased intracranial pressure (63%), visual impairment (47%), growth failure (26%), polyuria/polydipsia (16%), and weight gain (10.5%). As clinical signs at diagnosis, growth failure was observed in 11/18 patients, starting with a median lag of 1 year and 4 months before diagnosis. On ophthalmological examination, 27% of patients had papillary edema and 79% had visual impairment. When visual disturbances were found, the average preoperative volume was higher (p=0.039). Only 6/19 patients had gross total surgical resection. After the first neurosurgery, 83% experienced tumor recurrence or progression at a median time of 22 months. Eleven patients (73%) underwent postsurgical radiotherapy. At diagnosis, growth hormone deficiency (GHD) was the most frequent endocrine deficit (8/17) and one year post surgery, AVP deficiency was the most frequent deficit (14/17). Obesity was present in 13% of patients at diagnosis, and in 40% six months after surgery. There was no significant change in body mass index over time (p=0.273) after the first six months post-surgery. Conclusion CP is a challenging brain tumor that requires multimodal therapy and lifelong multidisciplinary follow-up including hormonal substitution therapy. Early recognition of symptoms is crucial for prompt surgical management. The management of long-term sequelae and morbidity are crucial parts of the clinical path of the patients. The results of this study highlight the fundamental importance of carrying out a complete assessment (ophthalmological, endocrinological, neurocognitive) at the time of diagnosis and during follow-up so that patients can benefit from the best possible care.